Don't let the pigeon drive the bus - Willems, Mo (Hyperion Books for Children, 2003)
No matter how hard he pleads and begs, the pigeon is not supposed to drive the bus while the driver is away, but pigeon tries every persuasive trick a young child knows to get you to say, "Yes."